miR-873-5p targets mitochondrial GNMT-Complex II interface contributing to non-alcoholic fatty liver disease - Pablo Fernández-Tussy; David Fernández-Ramos; Fernando Lopitz-Otsoa; Jorge Simón; Lucía Barbier-Torres; Beatriz Gomez-Santos; Maitane Nuñez-Garcia; Mikel Azkargorta; Virginia Gutiérrez-de Juan; Marina Serrano-Macia; Rubén Rodríguez-Agudo; Paula Iruzubieta; et al. (Elsevier, 2019)
Objective: Non-alcoholic fatty liver disease (NAFLD) is a complex pathology in which several dysfunctions, including alterations in metabolic pathways, mitochondrial functionality and unbalanced lipid import/export, lead to lipid accumulation and progression to inflammation and fibrosis. The enzyme glycine N-methyltransferase (GNMT), the most important enzyme implicated in S-adenosylmethionine catabolism in the liver, is downregulated during NAFLD progression. We have studied the mechanism involved in GNMT downregulation by its repressor microRNA miR-873-5p and the metabolic pathways affected in NAFLD as well as the benefit of recovery GNMT expression. Methods: miR-873-5p and GNMT expression were evaluated in liver biopsies of NAFLD/NASH patients. Different in vitro and in vivo NAFLD murine models were used to assess miR-873-5p/GNMT involvement in fatty liver progression through targeting of the miR-873-5p as NAFLD therapy. Results: We describe a new function of GNMT as an essential regulator of Complex II activity in the electron transport chain in the mitochondria. In NAFLD, GNMT expression is controlled by miR-873-5p in the hepatocytes, leading to disruptions in mitochondrial functionality in a preclinical murine non-alcoholic steatohepatitis (NASH) model. Upregulation of miR-873-5p is shown in the liver of NAFLD/NASH patients, correlating with hepatic GNMT depletion. Importantly, NASH therapies based on anti-miR-873-5p resolve lipid accumulation, inflammation and fibrosis by enhancing fatty acid β-oxidation in the mitochondria. Therefore, miR-873-5p inhibitor emerges as a potential tool for NASH treatment. Conclusion: GNMT participates in the regulation of metabolic pathways and mitochondrial functionality through the regulation of Complex II activity in the electron transport chain. In NAFLD, GNMT is repressed by miR-873-5p and its targeting arises as a valuable therapeutic option for treatment. Keywords: NASH, GNMT, Mitochondria, β-oxidation, Metabolism, microRNA